Sociology of Rural Life - Hillyard, Samantha (Berg Publishers, 2007)
From fox-hunting to farming, the vigour with which rural activities and living are defended overturns received notions of a sleepy and complacent countryside. Alongside these developments, the rise of the organic food movement has helped to revitalize an already politicized rural population. Over the years 'rural life' has been defined, redefined and eventually fallen out of fashion as a sociological concept - in contrast to urban studies, which has flourished. This much-needed reappraisal calls for its reinterpretation in light of the profound changes affecting the countryside. First providing an overview of rural sociology, Hillyard goes on to offer contemporary case studies that clearly demonstrate the need for a reinvigorated rural sociology. Tackling a range of contentious issues, this book offers a new model for rural sociology and reassesses its role in contemporary society.Providing an overview of rural sociology, this title calls for the reinterpretation of rural life in light of the profound changes affecting the countryside. It offers case studies that demonstrate the need for a reinvigorated rural sociology. Tackling contentious issues, it presents a model for rural sociology and assesses its role in society.Sam Hillyard is Lecturer in Sociology, School of Applied Social Sciences, Durham University.